Produtividade animal e características morfológicas do capim-tanzânia adubado com nitrogênio ou consorciado com estilosantes - Pinheiro, Alyson Andrade (2011)
The experiment was conducted in the northwestern region of Paraná, in Santo Inácio city, in order to assess the morphological composition, botany and accumulation of herbage mass, herbage dry matter available, tiller density, animal performance and economic evaluation rearing system in Tanzania grass pastures (Panicum maximum Jacq. cv. Tanzania-1) fertilized with nitrogen or intercropped with Stylosanthes Campo Grande (Stylosanthes spp.) It was used a randomized complete blocks with split plots design and three replicates of four treatments: Stylosanthes + Tanzania; Tanzania + 75 kg N ha-1; Tanzania + 150 kg N ha-1; Tanzania + 225 kg N ha-1. Plots were assessed stations. Plots were assessed stations. The total area of 12 ha of pasture was divided into three blocks, and these in turn subdivided into four plots (experimental units), making a total of 12 plots of 1 ha. The pasture was managed by the method of continuous stocking with variable stocking rate, keeping the sward height between 45 and 50 cm. For the maintenance of sward height a total of 36 Nelore were used with average weight of 230 kg, and in three testers animals per pen. To estimate the mass production and morphological composition, samples were collected close to the ground every 28 days. The evaluation of animal production was performed by weighing the animals every 28 days. The daily accumulation of forage was higher in summer followed by spring and fall with the application of 225 kg N ha/year. The consortium with stylosanthes provided mass accumulation similar to treatments with 75 and 150 kg N ha/year. The highest percentage of leaf spring was obtained using 150 and 225 kg N ha/year. The percentage of stems was lower in spring in the consottium with stylosanthes. The proportion of stylosanthes in the pasture was similar between seasons. The use of 150 and 225 kg N ha/year provided a larger number of alive tillers in the grass. The average daily gain in spring and summer was similar in treatments with 150 and 225 kg N ha/year, but in the fall, for the consortium with stylosanthes the use of 75 kg N ha/year was higher. The higher stocking rate was obtained in treatments with 150 and 225 kg N ha/year. All treatments showed positive economic results, however, the intercropped with stylosanthes was more lucrative.